Establishment and Transformation of Callus and Cell Suspension Cultures of the Prickly-Pear (Opuntia ficus-indica) - Llamoca-Zárate, R. M.; Campos, F. A. P.; Landsmann, J. (Journal of the Professional Association for Cactus Development, 2020)
Friable callus cultures were initiated from cotyledons and hypocotils of Opuntia ficus-indica. Propagation and growth of calli were observed on MS medium supplemented with 2,4-D, Pickloram and Casein. Cell transformation was achieved by particle bombardment. Kanamycin resistance, GUS expression, and PCR analyses indicated successful integration of foreign DNA.